Assessment of periodontal disease among the dental prosthetic and nonprosthetic wearers in an adult rural population in Mangalore taluk, South India - Mallika Sadanand Shetty; Saurabh Jain; Uma M Prabhu; Akshata G Kamath; Savitha Dandekeri; Mallikarjuna Ragher; Sanath K Shetty (Wolters Kluwer Medknow Publications, 2019)
Background: Oral health as an integral part of general health. Rural population neglect oral health as they lack awareness on oral diseases and also due to inadequate availability of dental services. There is a very high prevalence of chronic inflammatory periodontal disease in the rural Indian population, which is left untreated. Hence, this cross-sectional survey was taken up in the rural area of Mangalore taluk, Karnataka, India. Materials and Methods: A cross-sectional survey was carried out on 1312 participants aged 18 years and older. The prevalence of periodontal disease among the dental prosthetic and nonprosthetic wearers was assessed. The World Health Organization format was used to record the periodontal status and loss of attachment. Data collected were analyzed using chi-square test. P < 0.05 was considered as significant. Result: Of the 1312 included subjects, 520 were males (39.6%) and 792 were females (60.3%). Periodontal status showed that calculus was found to be high among all age groups. When the prevalence of periodontal disease was assessed among the prosthetic wearers, it was found that subjects wearing removable partial denture showed increased prevalence of periodontal pocket depth and attachment loss irrespective of age group, gender, and educational qualification. Conclusion: Lack of awareness among the individuals regarding periodontal diseases has been associated with consistently higher prevalence of periodontal diseases and treatment needs. Demographical studies need to be carried out at regular intervals, thus helping in planning the treatment needs nationwide for better oral health care in rural population.